(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Refractive laser surgery has absolute and relative contraindications. Among the relative ones is amblyopia and a history of strabismus. Caution should also be in cause of trauma, scar, or leukoma in the ablation site. Purpose. To present a case with regression of strabismic amblyopia after refractive surgery. Material and Methods. It was a pre-existing strabismus, which initially went unnoticed because it was a microtropia on left eye; the fixing right eye suffered a traumatic injury that produced a high ametropia and changed fixation. Results. The left eye developed excellent vision, but after the operation, somehow, momentarily the right eye became the fixator again, and the left eye saw very poorly. That situation was corrected quickly with right eye occlusion and lenses. That has happened because the eye had corrected its amblyopia for the years that the right eye was penalized. Once a good result was achieved, there was no change in fixation or visual loss. Conclusion. The change in ocular dominance and visual readjustment at the neuronal level that occurs in the postoperative period of refractive surgery stand out.